(untitled) (Indian Journal of Animal Production and Management, 2017)
A field survey was conducted to collect the information on neonatal management practices followed by the dairy animal owners in Tarai region of Uttarakhand. The results revealed that 100% of farmers clean mucous membrane of newborn calf immediately after birth. Around 74.38% allowed suckling within 15 minutes of birth and 23.12% between 30 minutes after birth. Majority of farmers 73.75% practiced feeding colostrum within half an hour of its birth and continuing upto the first five days. Practice of cutting and disinfection of navel cord after birth was uncommon (10%). Temporary identification method was common as compared to permanent type which were 87.50% and 12.50% respectively. Most of farmers feed their calves from two teats and 11.25% of farmers practice feeding of milk from all four teats. Dehorning was done by majority of the farmers (97.50%). Castration of male calves at 30-40, 40-50 and >50 days of age were practiced by 42.50, 27.50 and 23.75% of farmers respectively. Weaning of calves was done at 40-60 days of age by 83.12% of farmers.